Race, Representation, and Local Governments in the US South: The Effect of the Voting Rights Act - Bernini, Andrea; Facchini, Giovanni; Testa, Cecilia (Journal of Political Economy, 2023)
The Voting Rights Act of 1965 redefined race relations in the United States. Yet evidence on its effect on Black office holding remains scant. Using novel data on Black elected officials between 1962 and 1980, we assess the impact of the Voting Rights Act on the racial makeup of local governments in the Deep South. Exploiting predetermined differential exposure of Southern counties to the mandated federal intervention, we show that the latter fostered local Black office holding, particularly in the powerful county commissions, controlling local public finances. In the presence of election by district, covered counties experienced Black representation gains and faster capital spending growth.